2015
DOI: 10.1016/j.vetpar.2014.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Establishment rate of sheep gastrointestinal nematodes in farmed red deer (Cervus elaphus)

Abstract: To investigate the establishment of sheep gastrointestinal nematodes (GIN) in red deer, five red deer and five sheep aged 5-6 months were challenged with a mixed burden of sheep GIN at a rate of 327L3/kg bodyweight. The LSmean (SE) establishment rates (%) for Haemonchus contortus, Teladorsagia circumcincta, Cooperia curticei, Trichostrongylus spp. and Oesophagostomum+Chabertia spp. were 18.6 (0.03), 35.5 (0.04), 30.7 (0.04), 74.9 (0.05), 19.9 (0.06), respectively in sheep and 10.5 (0.03), 1.0 (0.04), 0.1 (0.04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, only a few experimental studies have shown effective successful cross-infection. For example, certain species of GI nematodes of sheep (administered orally as a solution of larvae) successfully established in farm red deer ( C. elaphus ), whereas others did not (Tapia-Escarate et al ., 2015). The abomasal nematode Ashworthius sidemi that commonly infects bison ( Bison bison ), red deer and roe deer ( Capreolus capreolus ) can also infest cattle grazing in the same pasture (Moskwa et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few experimental studies have shown effective successful cross-infection. For example, certain species of GI nematodes of sheep (administered orally as a solution of larvae) successfully established in farm red deer ( C. elaphus ), whereas others did not (Tapia-Escarate et al ., 2015). The abomasal nematode Ashworthius sidemi that commonly infects bison ( Bison bison ), red deer and roe deer ( Capreolus capreolus ) can also infest cattle grazing in the same pasture (Moskwa et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…H. contortus is one of the most pathogenic nematode parasites of sheep and is 165 widespread in Kazakhstan (Morgan et al, 2006). This parasite has been hypothesized as one of the most likely parasites to infect red deer if they have access to pasture where sheep have grazed (Tapia-Escarate et al, 2015) . Although our study was limited, there may be some patterns in the data.…”
Section: Discussionmentioning
confidence: 99%